Atheroma: Laporan Kasus - Yolanda Agtari; Wizar Putri Mellaratna (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This case report aims to describe the clinical features, management, and therapeutic outcomes of a patient with multiple atheromas. The method used was a case report of a 23-year-old male who presented to the Dermatology and Venereology Outpatient Clinic of RSUD Cut Meutia with multiple nodules on the back and a dome-shaped cyst on the right auricle that had been present for approximately nine years. The results showed that the lesions were initially asymptomatic but progressively enlarged and occasionally discharged a foul-smelling yellowish fluid, indicating secondary infection. Physical examination revealed skin-colored nodules with firm consistency and a central punctum on the auricle, as well as several papules and nodules on the back. The diagnosis was established as atheroma, with differential diagnoses including epidermoid cyst, lipoma, and steatocystoma. Management included oral antibiotics, antihistamines, topical fusidic acid antibiotics, supportive therapy, followed by planned complete surgical excision. In conclusion, accurate diagnosis and adequate surgical excision resulted in favorable clinical outcomes and are essential in preventing recurrence and complications of atheroma. Keywords: Atheroma, Epidermal Inclusion Cyst, Epidermoid Cyst, Secondary Infection, Surgical Excision